Drainage enhancement effects on a waterlogged Rhode Island (USA) salt marsh. (31st December 2019) - Raposa, Kenneth B.; Weber, Robin L.; Ferguson, Wenley; Hollister, Jeffrey; Rozsa, Ron; Maher, Nicole; Gettman, Alan
Abstract: Drainage enhancement (e.g., ditch digging, open-marsh water management, runnelling) has long been used to reduce tidal marsh soil waterlogging and surface ponding to promote salt hay production and mosquito control. Now it is also being used as a tool to enhance marsh resilience to sea-level rise despite a lack of studies that evaluate its effectiveness as an intervention approach. We therefore conducted a controlled field experiment to evaluate short-term responses to drainage enhancement of a Rhode Island (USA) salt marsh. Drainage enhancement elicited rapid physical changes in portions of the marsh including declines in water levels and marsh elevation, but the biological components examined (e.g., vegetation and bird community composition) were largely unaffected. In two of the four areas monitored, marsh surface inundation duration declined from >75% to 3–10% and low water levels dropped by 20 cm. Mean annual marsh surface elevation in monitoring plots increased 5 mm one year after drainage enhancement but dropped to 11 mm below initial conditions after three years. The decline in elevation varied among habitats, with the greatest decline (18 mm) found in areas dominated by Spartina alterniflora and/or bare ground. Vegetation community composition and % cover and heights of dominant species were unchanged, but areas that were initially bare had fully revegetated after three years. Drainage enhancement also had no effects on bird community composition or marsh sparrow ( Ammodramus spp.) density. Our study provides evidence that drainage enhancement can relieve waterlogging and some of its impacts without any apparent adverse effects on the composition and abundance of existing vegetation and bird communities. At the same time, it can induce a loss of marsh platform elevation that has the potential to offset declining water levels and inhibit high marsh enhancement. Finally, unanticipated findings from our study provide evidence that the effects of larger-scale drivers such as sea-level rise may predominate over localized responses to drainage enhancement itself. Highlights: An experiment was conducted to examine effects of salt marsh drainage enhancement. After three years, marsh elevation declined below initial conditions. Drainage enhancement had minimal effects on marsh vegetation and birds. Large-scale stressors, such as sea-level rise, may have effected project results.